Cost-consequence analysis of self-administration of medication during hospitalization: a pragmatic randomized controlled trial in a Danish hospital setting - Charlotte Arp Sørensen; Annette de Thurah; Marianne Lisby; Charlotte Olesen; Signe Bredsgaard Sørensen; Ulrika Enemark (SAGE Publishing, 2020)
Objectives: The objective of this study was to evaluate the costs and consequences of introducing "self-administration of medication" (SAM) during hospitalization as compared with nurse-led dispensing and administration of medication. Methods: This pragmatic randomized controlled trial was performed in a Danish Cardiology Unit. Patients ⩾18 years old capable of self-administering medication were eligible. In the intervention group, patients self-administered their medication. In the control group, medication was dispensed and administered by nurses. The implementation of SAM was used to evaluate the cost-consequences. The micro-costing analysis used the hospital perspective and a short-term incremental costing approach. The costs for medication, materials, and nursing time were included. Consequences included the dispensing error proportion, patients' perceptions regarding medication, satisfaction, and deviations in the medication list at follow-up. In addition, the number of readmissions and general practitioner (GP) contacts within 30 days after discharge was included. Results: The total cost (TC) per patient in the intervention group was 49.9€ (95% CI: 46.6-53.2) compared with 52.6€ (95% CI: 46.6-58.6) in the control group. The difference between the groups was not statistically significant ( p  = 0.09). Sensitivity analysis consistently showed TCs favoring the intervention. The dispensing error proportion was 9.7% (95% CI: 7.9-11.6) in the intervention group compared with 12.8% (95% CI: 10.9-15.6) in the control group. The difference was statistically significant ( p  = 0.02). The analysis also found changes in the perceptions regarding medication (indicating higher medication adherence), increased satisfaction, and fewer patients with deviations in the medication list at follow-up. No statistically significant differences between the groups in relation to readmissions and GP contacts within 30 days were observed. Conclusions: SAM seems to cost less although the cost difference was small and not statistically significant. As SAM had positive effects on patient outcomes, the results indicate that SAM may be cost-effective. Plain language summary Self-administration of medication: a research study of the costs and consequences Objectives To evaluate the costs and consequences of introducing "self-administration of medication" (SAM) during hospitalization compared to medication dispensed by nurses. Methods This research study included patients ≥18 years capable of self-administering medication and was performed in a Danish cardiology unit. Patients self-administered their own medication during hospitalization in the intervention group, whereas nurses dispensed and administered the medication in the control group. Patients were allocated between groups by randomization. The costs of SAM were analyzed from a hospital perspective and included costs for medication, materials, and nursing time. The consequences included the proportion of dispensing errors, patients' perceptions regarding medication, patient satisfaction, deviations in the medication list at follow-up, the number of readmissions and general practitioner (GP) contacts within 30 days after discharge. Results The total cost per patient was 49.9€ in the intervention group compared to 52.6€ in the control group ( p  = 0.09). The cost difference between groups was not significant. The proportion of dispensing errors was significantly lower in the intervention group compared to the control group. In addition the research study found changes in the perceptions regarding medication, increased satisfaction, and fewer patients with deviations in the medication list at follow-up. For readmissions and GP contacts within 30 days no significant differences between groups were found. Conclusion SAM cost less or equal to medication dispensing and administration by nurse. SAM had positive impacts on patient outcomes. Therefore, SAM may be cost-effective.